The effective length of columns in multi-storey frames. (1st November 2015) - Webber, A.; Orr, J.J.; Shepherd, P.; Crothers, K.
Highlights: The effective length method provides erroneous results in some situations. Two improvements to the method are proposed in this paper. Axial load in adjoining columns is incorporated in the effective length calculation. Buckling of adjacent columns is incorporated in the effective length calculation. The improvements provide results within 2% of that computed by software. Abstract: Codes of practice rely on the effective length method to assess the stability of multi-storey frames. The effective length method involves isolating a critical column within a frame and evaluating the rotational and translational stiffness of its end restraints, so that the critical buckling load may be obtained. The non-contradictory complementary information (NCCI) document SN008a (Oppe et al., 2005) to BS EN 1993-1 (BSI, 2005) provides erroneous results in certain situations because it omits the contribution made to the rotational stiffness of the end restraints by columns above and below, and to the translational stiffness of end restraints by other columns in the same storey. Two improvements to the method are proposed in this paper. First, the axial load in adjoining columns is incorporated into the calculation of the effective length. Second, a modification to the effective length ratio is proposed that allows the buckling load of adjacent columns to be considered. The improvements are shown to be effective and consistently provide results within 2% of that computed by structural analysis software, as opposed to the up to 80% discrepancies seen using the NCCI (Oppe et al., 2005).